Sistem Informasi Akuntansi Pada Salon Putri Menggunakan Metode ERP Berbasis Web - Tiara nur safitri; Mustaqiem - (LPPM UBHINUS MALANG, 2023)
All systems that run at Putri's salon are still done manually, so it takes a long time to process it and data writing errors often occur. Therefore, this salon really needs a computerized system in the transaction process so that it is recorded accurately and quickly in a computer program. The purpose of this research is to design an information system for calculating and reporting employee salaries and a system that can present financial reports in the form of accounting. This application development method used in data collection is observation, interviews, and literature study. The design method used is Data Flow Diagram (DFD), the programming language used is PHP and MySQL database. This system includes several menus, namely the main page, master data, transactions and reporting menus. From the test results concluded that the expected functions all work as desired. With the construction of the Salon Putri accounting information system, it will facilitate the performance of salon owners in managing activities and analyzing financial statements at Salon Putri better.